Сюжетные особенности романа Д. Томаса «Белый отель» - Джанбек, А.Д.; Бондаренко, Л.В. (Культура народов Причерноморья, 2014)
Творчество Д.Томаса, одного из наиболее значимых современных британских прозаиков,
рассматривается в контексте постмодернистской литературы, для которой характерна
фрагментарность и многосложность нарратива. В статье предлагается новый взгляд на проблему,
согласно которому, сюжетная структура произведения определяет не только формальные, но и
смысловые характеристики текста. Исследование проведено на основе комплексного подхода,
сочетающего традиционные и новые подходы и методы, такие как типологический и культурно-
исторический подходы, герменевтический и сравнительный методы, структурный, рецептивный и
метод тщательного прочтения.
Д. Томас строит рассказ на основе сочетания хроникального и концентрического сюжетов, используя
повествование в форме письма, открытки, вырезки из газеты, литературный прием « flashback», что
придает динамичность тексту и способствует более глубокому раскрытию психологических
переживаний героев. У статті розглядаються сюжетні особливості постмодерністського роману Д. Томаса
«Білий готель». В романі Д. Томас вміло будує текст завдяки комбінації хронікального та
концентричного видів сюжету, використовуючи оповідання у формі листа, уривку з газети, листівки та
літературний прийом «флешбек». «Білий готель» як сучасна постмодерністська англійська
відрізняється своєю фрагментарністю наратива та складністю сюжету. У статті запропоновано
новий погляд на проблему сюжету, завдяки якому сюжетна структура твору обгрунтовує не тільки
формальні, а також смислові характеристики тексту. Дослідження здійснювалось на підставі
традіційних та нових підходів та методів, якi становлюють сутність комплексного підходу
дослідження, заснованного на зв’язку цих методів, а саме – типологiчного та культурно-історичного
підходів, герменивтичного та порівняльного методів, структурного та рецептивного методів та
метод “наполегливого читання”. Складна сюжетна структура надає динамічності тексту та сприйяє
глибокому розумінню психологiчних характерів героїв. The works of Donald Thomas, who is considered to be one of the most prominent British novelists,
are viewed in the context of postmodern literature, which is characterized by fragmentation and multilayered
narrative. The article features a new outlook on the plot structure of a modern novel, according to which the plot
composition and types of narrative shape the form and influence the content of the text. The research is
conducted on the basis of the complex approach, combining traditional and new approaches and methods, such
as typological and historic-cultural approaches, hermeneutic and comparative methods, structural, receptive
and method of “close reading”.
D. Thomas conducts the narration on the grounds of the combination of the two types of plots – chronicle and
concentric, employing such forms of narration as letters postcards, newspaper cut-outs, “flashback”, a popular
literary device. That makes the text dynamic and enhances the process of revelation of the psychological
problems of the characters.
An intricate plot and multilayered composition of the novel reflects its deep psychological, social and political
meaning. “White Hotel” encompasses traits of the psychological novel and thriller framed in the postmodern
narration. The novel consists of the prologue and six parts, featuring the life of a Russian singer in the
background of historical events of the first half of the 20th century, including Holocaust and fascist occupation of
Europe. Personal tragedy reveals the national tragedy marked in history as the Second World War. The events
develop mostly in Europe in artistic circles that gives the reader a deep insight into the human soul making it
explicit with the help of psychological analysis practiced by Z. Freud, another main character of the novel. Thus
there are two main plot lines in the text – the personal and the social one, framing the narrative.